MDM : Fundamentals, Security, and the Modern Desktop: Using Intune, Autopilot, and Azure to Manage, Deploy, and Secure Windows 10 - Moskowitz, Jeremy (John Wiley & Sons, Inc. (trade) : Sybex, 2019)
A must-read for IT Admins leveraging Modern Management with MDM, this book teaches you MDM fundamentals, essential troubleshooting techniques, and how to manage your enterprise desktops. --